A COMPARISON STUDY OF HAIR TONIC AND GEL FORMULATION OF ANGIOPTERIS EVECTA AS A HAIR GROWTH STIMULANT - Mustarichie, Resmi; Dolih-Gozali; Wicaksono, Imam Adi; NAFIS, FERIS DZAKY RIDWAN (International Journal of Applied Pharmaceutics, 2019)
Objective: Previous research has proven that the water fraction of the Angiopteris evecta root has hair growth activities. The objective of this research was to determine the formula of gel and hair tonic preparations of pakis munding (Angiopteris evecta L.) which met the requirements as a pharmaceutical preparation, good and effective in stimulating hair growth. Methods: Formulation of hair tonic and gel preparations were made using 7.5, 10.0, and 12.5 % of A. Evecta root water extracts as active compounds. The formulation of the two preparations was based on the standard formulation method. The evaluation and formulation test were carried out by organoleptic examination and homogeneity, pH, viscosity, scattering power test, stability test, and safety test based on the standard preparations including Indonesian pharmacopeia. Statistical tests were carried out on both formulas against rabbits based on the modification of the Tanaka method. Comparison of statistics on both formulas was also carried out. Results: It was found both formulas fulfill standard requirements as pharmaceutical preparations. Statistically, the best activity in hair tonic preparations was at a concentration of 12.5% and for gels at a concentration of 10.0% ethanol extract seen from measurements of hair length. Statistically, using the Independent T-test to find out the significant differences in the average hair length on hair tonic and gel, it was found there was no significant difference between the two formulas. It was found that the best formula for hair tonic and gel was in the addition of 10.0% and 12.5% extracts, respectively. Conclusion: The results obtained in this research work clearly indicated that both hair tonic and gel formulas of A. evecta root water extract may be used as stimulating hair growth.